Tenant mix structure in shopping centres: some empirical analyses from Poland - Bartłomiej Marona; Anna Wilk (Entrepreneurial Business and Economics Review, 2016)
Objective: The objective of this paper is to find an ideal tenant mix structure for the current shopping centres in Upper Silesian Urban Area Region in Poland, taking under consideration consumer preferences and behaviour.